2020
DOI: 10.1123/ijspp.2019-0425
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Stress in Injured and Ill Elite International Olympic Rowers

Abstract: Background: Identifying strategies that reduce the risk of illness and injury is an objective of sports science and medicine teams. No studies have examined the relationship between oxidative stress (OS) and illness or injury in international athletes undergoing periods of intensified training and competition. Purpose: The authors aimed to identify relationships between illness, injury, and OS. Methods: A longitudinal, observational study of elite male rowers (n = 10) was conducted over 18 weeks, leading into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Regular, intense training and competition, without adequate recovery or reduced training load, can increase the level of oxidative stress markers that contributes to increased risk of illness and injuries in athletes [ 43 ]. An increase in the oxidative stress index (OSI) in elite Olympic rowers was related to higher injury and illness rates during the competition phase of their season [ 44 ]. The marked decreases in ASA, AcP and CK facilitated by WBC or PBC could potentially decrease injury and illness risks over long, intense training periods when used chronically by athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Regular, intense training and competition, without adequate recovery or reduced training load, can increase the level of oxidative stress markers that contributes to increased risk of illness and injuries in athletes [ 43 ]. An increase in the oxidative stress index (OSI) in elite Olympic rowers was related to higher injury and illness rates during the competition phase of their season [ 44 ]. The marked decreases in ASA, AcP and CK facilitated by WBC or PBC could potentially decrease injury and illness risks over long, intense training periods when used chronically by athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma Antioxidant Capacity was determined using the FORD test (Callegari, Catellani, Italy) (Lewis et al, 2020;Pavlatou et al, 2009), a colorimetric essay that relates the discoloration of the sample with antioxidants concentration, according to Lambert-Beer law (Pavlatou et al, 2009) Perception of fatigue and pain was measured using a 150-mm visual analogue scale (VAS) (Mündermann et al, 2002). The scales were labelled from the left as "absence of fatigue/pain" (0 mm) to the right as "highest fatigue/pain imaginable" (150 mm).…”
Section: Methodsmentioning
confidence: 99%
“…However, PE-induced health benefits can be limited by the overproduction of ROS/RNS. Excessive ROS/RNS can cause an extensive alteration in redox homeostasis, damage biomolecules and decrease skeletal muscle force, overtraining, muscle injury, and illness [86][87][88]. A considerable number of studies have reported that not only a sedentary lifestyle but also short-term exercise of high intensity or severe aerobic or anaerobic PE not preceded by training can primarily increase ROS/RNS production, elevating the inflammatory processes in the cells and contribute to OS [89][90][91].…”
Section: Exercise and Oxidative Stressmentioning
confidence: 99%